CHEMICAL, BIOLOGICAL AND HYDROLOGICAL CONTROLS ON THE 14C CONTENT OF COLD SEEP CARBONATE CRUSTS: NUMERICAL MODELING AND IMPLICATIONS FOR CONVECTION AT COLD SEEPS - Aloisi G.; Wallmann K.; Haese R.R.; Saliège J.-F. (My University, 2004)
Understanding the hydrology of cold seep environments is crucial to perform accurate estimates of fluid and chemical fluxes at sedimentary wedges. Shallow convection processes may affect fluid flux estimates and could favor the destabilization of gas hydrate accumulations, increasing the sediment-ocean methane flux. Evidence for the occurrence of convection at cold seeps, however, is still limited. We use the concentration of 14C (D14C) in carbonate crusts formed at cold seeps of the eastern Mediterranean Sea as a tracer for convective recirculation of seawater-derived fluids. A numerical model is applied to investigate the controls on 14C incorporation in cold seep carbonates. Our simulations show that increased amounts of CH4 in the expelled fluids result in elevated crust D14C, while high Ca2+ and HCO3− concentrations produce the opposite effect. Convection is the only transport process that can significantly increase crust D14C. Advection, bioirrigation, eddy diffusion and bioturbation instead, have little effect on, or produce a decrease of, crust D14C. In addition, the presence of old or modern carbon (MC) in host sediments prior to cementation and the 14C-decay associated to the time needed to form the crust contribute in defining the D14C of carbonate crusts. We then use the model to reproduce the 14C content of the eastern Mediterranean Sea crusts to constrain the chemical and hydrological conditions that led to their formation. Some crusts contain relatively low amounts of 14C (−945.0